Artikelopposition im Deutschen und Artikellosigkeit im Polnischen aus der Sicht der Textstruktur - Gaca, Alicja (Studia Germanica Posnaniensia, 2018)
In the article the author considers opposition of articles ein: der in the German language and possibilities of its equivalence in the structure of text in the Polish language. Analysing lexical, morphological and syntactic (and prosodic) means of linguistic expression as exponents of intertextual system of indication ( = of anaphora relation) the author establishes for the German articles equivalent semantic oppositions on various levels of the Polish language system.